2018
DOI: 10.7554/elife.30246
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic clustering of dynamin-amphiphysin helices regulates membrane constriction and fission coupled with GTP hydrolysis

Abstract: Dynamin is a mechanochemical GTPase essential for membrane fission during clathrin-mediated endocytosis. Dynamin forms helical complexes at the neck of clathrin-coated pits and their structural changes coupled with GTP hydrolysis drive membrane fission. Dynamin and its binding protein amphiphysin cooperatively regulate membrane remodeling during the fission, but its precise mechanism remains elusive. In this study, we analyzed structural changes of dynamin-amphiphysin complexes during the membrane fission usin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
36
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 52 publications
6
36
0
Order By: Relevance
“…4G). This establishes an interesting similarity between FtsZ and dynamin, in which GTP hydrolysis also triggers a super-constricted state, favoring fragmentation and clustering (19,20). We conclude that these torques represent a robust constriction mechanism for cylindrically shaped membranes.…”
supporting
confidence: 55%
“…4G). This establishes an interesting similarity between FtsZ and dynamin, in which GTP hydrolysis also triggers a super-constricted state, favoring fragmentation and clustering (19,20). We conclude that these torques represent a robust constriction mechanism for cylindrically shaped membranes.…”
supporting
confidence: 55%
“…In fluorescence experiments with pre-formed tubules pulled with optical tweezers from GUVs, the membrane coverages 44 ± 27% of endophilin N-BAR domains and 37 ± 9% of β2 centaurin BAR domains have been measured along the tubules (45). Sparse but regular arrangements on membrane tubules have been recently observed for dynamin-amphiphysin complexes (46).…”
Section: Discussionmentioning
confidence: 91%
“…In recent years, several structural and theoretical models have proposed that tilting of the PH domains promotes membrane fission by applying torque to the lipid bilayer and therefore, plays a key role in the membrane fission function of dynamin (20)(21)(22). Additionally, evidence, such as decrease in the fluorescence of labeled dynamin scaffolds (11), variations in the conductance of dynamin-coated tubes (12), and clustering of dynamin-amphiphysin complexes (23), suggests that GTP hydrolysis results in a partial breakup of the dynamin helix, indicating that the equilibrium length of the constricted oligomer is reduced (24).…”
mentioning
confidence: 99%
“…Recently, high-speed atomic force microscopy (AFM) has been utilized to characterize the morphology of the membranedynamin system (23,25). The high spatial and temporal resolutions of these measurements have revealed that GTP hydrolysis results in a dynamic alteration of the oligomer's shape (25).…”
mentioning
confidence: 99%